Astaxanthin ameliorates lipopolysaccharide-induced acute lung injury via inhibition of inflammatory reactions and modulation of the SOCS3/JAK2/STAT3 signaling pathways in mice. Issue 22 (24th October 2022) - Zhu, Li; Wu, Huihui; Ma, Zhenbo; Dong, Decheng; Yang, Ze; Tian, Jing
Abstract : The results showed that astaxanthin had a protective effect on LPS-induced acute lung injury in mice, and its protective mechanism was through activating the SOCS3/JAK2/STAT3 signaling pathway. Abstract : Acute lung injury (ALI) is a systemic inflammatory process. A large number of studies have shown that astaxanthin (ASTA) has strong anti-inflammatory effects and almost non-toxic side effects. The purpose of this study was to explore the effect of ASTA on lipopolysaccharide (LPS)-induced ALI in mice and its underlying mechanism. The result showed that compared with the LPS group, the expression levels of the respiratory resistance (Re), inspiratory resistance (Ri), dynamic lung compliance (Cdyn), wet/dry weight (W/D) ratio, albumin (BA/SA) ratio and myeloperoxidase (MPO) activity in the ASTA pretreatment group were significantly reduced, and total cell, neutrophil and macrophage counts were significantly decreased. HE staining results showed that alveolar interstitial edema, bleeding and erythrocyte exudation were reduced. Compared with the LPS group, the percentage of Th17 cells and the content of interleukin (IL)-17 and tumor necrosis factor-α (TNF-α) in the ASTA pretreatment group were significantly decreased, while the content of the transforming growth factor (TGF)-β and the percentage of Treg cells were significantly increased. Western blot analysis showed that ASTA could up-regulate the expression level of the suppressor of cytokine signaling-3 (SOCS3) and down-regulate the expression levels of phosphorylated Janus kinase 2 (p-JAK2), phosphorylated signal transducer and activator of transcription 3 (p-STAT3) in lung tissue. The results showed that ASTA had a protective effect on LPS-induced acute lung injury in mice, and its protective mechanism was through activating the SOCS3/JAK2/STAT3 signaling pathway, promoting Treg cell differentiation and reducing inflammatory reactions and Th17 cell differentiation, which provided a theoretical basis for the clinical treatment of ALI.